Gradation Design and Performance Evaluation of High Viscosity Asphalt Mixtures. (30th December 2020) - Hu, Xudong; Li, Sheng; Yao, Hui; Wang, Hui; Xu, Mei; Cao, Dandan; Mohd Hasan, Mohd Rosli; Duan, Cong; Zhang, Ran
Abstract : The property of asphalt binder plays an important role in the performance of asphalt mixture. The natural rubber additive (NRA) was recommended as a modifier in the preparation of high viscosity asphalt (HVA) binder. Then, the gradation named LASTIKA-13 was adopted to design the high viscosity asphalt mixture (HVAM) according to the orthogonal test analysis and the optimized gradation. The performance of the proposed HVAM was evaluated through a series tests including the permanent deformation at high temperature, moisture stability, low-temperature cracks, and bending fatigue test. The results indicate that the proposed modified asphalt binder shows a comparable property with the conventional modified asphalt binder. The proposed HVAM with the NRA modifier has a superior performance to other conventional mixtures in the temperature susceptibility and resistance to moisture damage. Furthermore, the proposed HVAM was less sensitive to the temperature change and has good performance in terms of resistance to low-temperature cracks, bonding characteristics, and fatigue behaviors.